Landslide Hazard Mapping in Cilegon With Geographic Information System (GIS) - Mina, Enden; Kusuma, Rama Indera; Fathonah, Woelandari; Rafabi, Muhammad Iqbal Beckham (JURUSAN TEKNIK SIPIL, 2024)
Natural disasters are disasters caused by events caused by nature. One of the natural disasters that continues to lurk in society is landslides. Landslides are the process of ground movement in an inclined or vertical direction from its original position as a result of gravity. Disaster Risk Assessment is an integrated mechanism to provide a comprehensive picture of a region's disaster risk by analyzing the Danger of Natural Disaster, Threat Level, Loss Level and Regional Capacity of dealing with threats of natural disaster. Geographic Information System (GIS) is a computer-based system used to store and display geographic information. GIS systems are designed for collecting, storing and analyzing geographic data at a location. Cilegon is a municipality in Banten Province, Indonesia. Cilegon is at the northwestern tip of the island of Java, on the edge of the Sunda Strait, with an area of 16.259 hectares, with a population of 450,271 people.